Analisis Hubungan Manajemen Modal Kerja dan Kinerja Keuangan : Perspektif Profitabilitas - Ardhan Ardiansyah Kawakibi; Mohamad Yusuf Kurniawan (Lembaga Pengembangan Kinerja Dosen, 2025)
The purpose of this paper is to determine and analyze the effect of working capital management to firms’ profitability. This study describes the effect of Days of Receivable, Days of Inventory, Days of Payable, and Cash Conversion Cycle on Return on Assets (ROA) of firms. This research uses descriptive quantitative method performed on plastic manufacturing firms listed on the Indonesia stock exchanges during five periods using data collected from the annual financial statements of the firm. The data are analyzed using multiple linear regression analysis. The results of this research show that, partially, period of receivable and period of inventory have a significant and positive effect on profitability. This means that if the period of receivable and the periods of inventory increases, the profitability will increase. A significant and negative effect on profitability is inflicted by period of debt and cash conversion cycle. This means that if the period of debt and cash conversion cycle increases, the profitability of the firms will decrease.